An investigation on the efficiency of solid oxide fuel cells - Fraser James Forbes Hancock. (2013)
Power generation companies and large scale industries, due to current legislation, are under pressure to generate electricity more efficiently and with less carbon emissions. Fuel cells and in particular solid oxide fuel cells in combined heat and power cycles could be a viable method to achieve this.